SOSIALISASI STIMULASI TUMBUH KEMBANG ANAK DI POSYANDU DESA RANGGON KABUPATEN KARAWANG - Lismayanti, Desty; Sarini, Sarini; Kharisma, Dinda; Hafid, Indah Fitria (LP2M STP Mataram, 2024)
Child development is a process of change that occurs in children until adolescence. These changes range from physical aspects (height, weight, motor skills) to cognitive (thinking, learning, language) to social and emotional (interacting with others, coping with emotions). Stunting is a condition where a child's height is small or too short compared to the standard height for their age. Stunting can have short-term and long-term impacts on growth and development so it must be prevented or treated. The purpose of this activity is to provide education to mothers at the Posyandu in Cengkong village about increasing stimulation of child growth and development and providing balanced nutrition to their children. The methods used include education through lectures, discussions, simulation exercises, and assistance from cadres and Sehati University of Indonesia community service nursing lecturer team to families who have babies / toddlers with a high risk of stunting. Participants in this community service activity consisted of Posyandu cadres and parents with babies/children who were at high risk of stunting and who had experienced stunting based on their Growth charts sheet. continuously, especially as an effort to increase the knowledge and skills of mothers, as one of the efforts to prevent and handle stunting